مدى إمكانية تطبيق نظام إدارة الجودة الأ يزو9001 في مدارس التعليم ما بعد الأساسي بمحافظة شمال الباطنة في سلطنة عمان - Ahmed Ali Mubarak Al-Kaabi (Universiti Sains Islam Malaysia, 2024)
This research discusses how the quality management system ISO 9001 can be applied to the education schools beyond primary in North Batinah. The aim of the research is to shed light on the quality management systems and to measure the awareness of workers in the schools of education beyond the basic quality management system as well as to study the possibility of applying the system quality management ISO 9001 in education schools beyond primary with visualizing a proposal for the implementation of the system. The researcher used descriptive survey field which included search tool (resolution). 300 sample population of the study were taken and it has been found that staff awareness in education schools beyond primary quality system averages at (68.634 %) , and the possibility of the application was high with a percentage of (74.614 %), while the vertebrae resource management education schools beyond primary was moderate with a percentage of ( 62.729 %) . In addition, existing services in schools of education have reached beyond the basic specifications to a high degree with a percentage of (69.266 %). While the results of follow –up, analysis and optimization was also high with a percentage of ( 70.99 %). Thus, the study recommended the application of a quality management system in school mentioned subject that the partial application of the system initially in certain schools. Nevertheless, the application of the system should eventually expand to include the rest of the schools. In addition , the need to develop human resources is vital to cope with the improvements and to guarantee sufficient improvements in the fields and to create a substantial climate to work in .The development of the structure is aided by the participation of specialists to ensure quality is reached and to meet the worker needs. Nevertheless , an important point is the need to establish a department for quality in education which has a specialist for quality working to oversee the audit and to provide the culture necessary for the quality as well as the development of the work to reach the minimum system standards. However , the standards maybe flexible and should aim to describe the critical functions and operations, as well as the rehabilitation and training of personnel in the schools applicable on the quality management systems, the requirements of the International Standard ISO 9001:2008 and missions for the rehabilitation of human cadres in quality management.